Pemanfaatan YouTube sebagai Media Penyebaran Informasi dalam Upaya Mengurangi Kasus Stunting - Kartinawati, Erwin; Purwasito, Andrik; Suwarni, Anik; Prajoko, Roso (Universitas Merdeka Surabaya, 2025)
Stunting is a condition in which a child's growth and development are impaired, resulting in a delay in physical and mental growth. We can observe characteristics in its physical condition that differ from those of children in general. The problem of stunting is not only the government's responsibility but also a problem that must be solved together, as it can affect the nation's and state's quality. The efforts we have made to help the government reduce stunting rates include community service programs and the use of YouTube as a Medium for Disseminating Health Information, especially related to stunting. Community service activity was carried out in Kalijirak Village, Tasikmadu District, Karanganyar Regency, Central Java, by providing training to 28 Posyandu cadres. Cases of stunting in children under the age of five (Toddlers) in the village were said to be still relatively high but not triggered by malnutrition. The number of mothers who marry early was said to be one of the causes, so it affected the level of health knowledge and parenting patterns for children. Efforts to increase health knowledge, particularly regarding the prevention of stunting, have been undertaken by the government through conventional methods, such as face-to-face communication. The number of health officers was reportedly disproportionate to the wide coverage area. Therefore, YouTube can be utilized as a medium to help disseminate health information, particularly in increasing the local community's Knowledge to reduce stunting cases. The training results indicated that the community had successfully produced and disseminated health information via YouTube as part of an effort to reduce and prevent cases of stunting.